2023
DOI: 10.3390/genes14040895
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Biological Roles of Circular RNAs in the Immune Systems of Insects to Pathogen Invasion

Abstract: Circular RNAs (circRNAs) are a newly discovered class of endogenously expressed non-coding RNAs (ncRNAs). They are highly stable, covalently closed molecules that frequently exhibit tissue-specific expression in eukaryotes. A small number of circRNAs are abundant and have been remarkably conserved throughout evolution. Numerous circRNAs are known to play important biological roles by acting as microRNAs (miRNAs) or protein inhibitors (‘sponges’), by regulating the function of proteins, or by being translated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 135 publications
0
1
0
Order By: Relevance
“…CircRNA was first identified by using electron microscopy in 1976 but did not attract much attention then. Only in recent years, with the development of the high-throughput sequencing technique and the discovery of a series of circRNAs, researchers have gradually realized the specificity of circRNA and its functional importance in vivo ( Sanger et al, 1976 ; Jeck et al, 2013 ; Memczak et al, 2013 ; Abbas et al, 2023 ). With the development of technology, the functions of circRNA have been found not only to act as a miRNA sponge that regulates the transcriptional level but also to encode proteins and regulate protein binding at different levels ( Qu et al, 2015 ; Kristensen et al, 2019 ).…”
Section: Regulation Of Bmnpv Infection In the Silkworm By Ncrnasmentioning
confidence: 99%
“…CircRNA was first identified by using electron microscopy in 1976 but did not attract much attention then. Only in recent years, with the development of the high-throughput sequencing technique and the discovery of a series of circRNAs, researchers have gradually realized the specificity of circRNA and its functional importance in vivo ( Sanger et al, 1976 ; Jeck et al, 2013 ; Memczak et al, 2013 ; Abbas et al, 2023 ). With the development of technology, the functions of circRNA have been found not only to act as a miRNA sponge that regulates the transcriptional level but also to encode proteins and regulate protein binding at different levels ( Qu et al, 2015 ; Kristensen et al, 2019 ).…”
Section: Regulation Of Bmnpv Infection In the Silkworm By Ncrnasmentioning
confidence: 99%
“…It has been suggested that circRNAs are crucial regulators in immune defense of insects against pathogens or parasites [60]. Hu et al [61] investigated the circRNA expression in the gut tissue of Bombyx mori following BmNPV challenge, and the results showed that circRNAs potentially regulate the genes annotated to ubiquitin, apoptosis, and endocytosis signaling pathways by the ceRNA axis.…”
Section: Discussionmentioning
confidence: 99%
“…Circular RNAs play roles in gene expression by modulating transcription in the nucleus and regulating translation in the cytoplasm. In the nucleus, circRNAs play a diverse biological role including chromatin looping, transcription regulation, and alternative splicing [170][171][172][173][174]. Circular RNAs can form three-stranded structures harboring a DNA:RNA hybrid named R-loops with their producing locus to impact transcription [171].…”
Section: Circular Rna (Circrna)mentioning
confidence: 99%